Twelfth-grade students’ interest in pursuing higher education in the biology education study program - Titin Titin; Eko Sri Wahyuni; Afandi Afandi; Mas Akhbar Faturrahman; Indah Supriyanti (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2025)
The decision of senior high school students in continuing their studies in specific higher education study programs, such as Biology Education, plays an essential role in preparing qualified future teachers and improving the quality of education in the region. However, this decision is closely related to students’ interests, which strongly influence their study program choices. This research aims to determine the level of interest among twelfth-grade students at State Senior High School 1 of Teluk Pakedai in continuing their studies in the Biology Education study program. This research is classified as descriptive quantitative. The sample in this research consisted of 49 twelfth-grade students at State Senior High School 1 of Teluk Pakedai, taken through total sampling. Data were collected using a closed-ended questionnaire covering seven aspects: “Happiness,” “Desire,” “Attention,” “Necessity,” “Expectation,” “Encouragement,” and “Willingness.” The data that has been collected is analyzed in the form of percentages and categorized into seven categories, including none to all of the sample. From the research conducted, it is known that 72.4% (most of the sample) of twelfth-grade students at State Senior High School 1 of Teluk Pakedai are interested in continuing their studies in the Biology Education study program. These findings suggest that increasing students’ awareness and motivation toward the Biology Education study program is essential. This can be achieved through academic counseling, alumni involvement, and activities introducing teaching career prospects.Abstrak. Keputusan peserta didik sekolah menengah atas (SMA) untuk melanjutkan studi mereka di program studi pendidikan tinggi tertentu, seperti Pendidikan Biologi, memainkan peran penting dalam mempersiapkan calon guru berkualitas dan meningkatkan mutu pendidikan di daerah. Namun, keputusan tersebut sangat berkaitan dengan minat peserta didik, yang secara signifikan memengaruhi pilihan program studi yang diambil. Penelitian ini bertujuan untuk menentukan tingkat minat peserta didik kelas XII di SMA Negeri 1 Teluk Pakedai untuk melanjutkan studi di program studi Pendidikan Biologi. Penelitian ini tergolong kuantitatif deskriptif. Sampel pada penelitian ini adalah peserta didik kelas XII di SMA Negeri 1 Teluk Pakedai yang berjumlah 49 orang, diambil dengan teknik pengambilan sampel jenuh. Data dikumpulkan menggunakan angket tertutup yang mencakup tujuh aspek: “Perasaan Senang”, “Keinginan”, “Perhatian”, “Kebutuhan”, “Harapan”, “Dorongan”, dan “Kemauan”. Data yang telah dikumpulkan dianalisis dalam bentuk persentase dan dikategorikan menjadi tujuh kategori yang mencakup tak seorang pun sehingga seluruh sampel. Berdasarkan penelitian yang telah dilakukan, diketahui bahwa 72,4% (sebagian besar sampel) peserta didik kelas XII di SMA Negeri 1 Teluk Pakedai berminat melanjutkan studi ke program studi Pendidikan Biologi. Temuan ini menunjukkan bahwa peningkatan kesadaran dan motivasi peserta didik terhadap program studi Pendidikan Biologi sangat diperlukan. Hal ini dapat dilakukan melalui kegiatan bimbingan akademik, keterlibatan alumni, dan aktivitas yang memperkenalkan prospek karier sebagai pendidik.